2019
DOI: 10.1101/751305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of C-terminal amino acid composition on protein expression in bacteria

Abstract: The C-terminal sequence of a protein is involved in processes such as efficiency of translation termination and protein degradation. However, the general relationship between features of this C-terminal sequence and levels of protein expression remains unknown. Here, we identified C-terminal amino acid biases that are ubiquitous across the bacterial taxonomy (1582 genomes). We showed that the frequency is higher for positively charged amino acids (lysine, arginine) while hydrophobic amino acids and threonine a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…We found that hydrophobic sequences as short as a single residue can promote Lon-dependent degradation of functional proteins in M. pneumoniae. In this line, we have recently shown that protein abundances can be influenced by the identity of the last C-terminal amino acid, with hydrophobic residues associated with faster degradation rates (Weber et al, 2020). In vitro studies performed with the E. coli Lon protease has suggested that sequences rich in aromatic residues that are accessible in misfolded proteins act as Lon recognition signals (Gur & Sauer, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that hydrophobic sequences as short as a single residue can promote Lon-dependent degradation of functional proteins in M. pneumoniae. In this line, we have recently shown that protein abundances can be influenced by the identity of the last C-terminal amino acid, with hydrophobic residues associated with faster degradation rates (Weber et al, 2020). In vitro studies performed with the E. coli Lon protease has suggested that sequences rich in aromatic residues that are accessible in misfolded proteins act as Lon recognition signals (Gur & Sauer, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To model amino acid substitutions and quantitatively predict their impact on protein stability, we run the command BuildModel that predicted a ΔΔG of 3.228 kcal/mol for the F89E mutation. Disruption of activity of the Fluc variant was confirmed by using the ONE-Glo ™ Luciferase Assay System (Promega) as previously described (Weber et al, 2020). Primers and Gibson cloning strategy to generate the F89E luc variant are detailed in Reagents and Tools Table (Appendix Tables S3 and S2).…”
Section: Construction Of An Unstable Variant Of the Luciferase Reportermentioning
confidence: 99%
See 2 more Smart Citations
“…Wildtype M. pneumoniae strain M129 (WT) was grown in modified Hayflick medium ( 31 ) at 37°C under 5% CO 2 in tissue culture flasks. To generate M. pneumoniae mutant libraries, 2 μg of mini-transposon plasmid DNA (pMTnCat_BDPr) was electroporated as previously described ( 32 ). The resulting transformants were selected during 5 days in 5 ml of culture medium supplemented with 20 μg/ml of chloramphenicol, and then harvested in 1 ml of fresh medium.…”
Section: Methodsmentioning
confidence: 99%